2017
DOI: 10.1136/heartasia-2016-010854
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of exercise-induced premature ventricular complexes: a systematic review and meta-analysis of observational studies

Abstract: Background Exercise-induced premature ventricular complexes (EI-PVCs) are common during exercise stress tests. Their optimal management and prognostic significance remain uncertain. Aim To perform meta-analysis of observational studies on the prognostic significance of EI-PVCs. Methods A search was conducted on Medline and Embase. Inclusion criteria were observational studies comparing the prognosis of patients with and without EI-PVCs whilst exclusion criteria were studies without confounder adjustment and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
3
15
3
Order By: Relevance
“…141,144 The benefit of anticoagulating patients structural alterations that may be associated with the undesired outcome of major ventricular arrhythmias or sudden death ( Table 5). 151,152 There is no absolute threshold of the number of PVCs that can be used as a cut-off for underlying disease and hence should trigger further investigations. A study in apparently healthy athletes has shown that in those with >2000 PVC per day, there was a 30% risk of finding underlying heart disease.…”
Section: Consensus Statements Symbol Referencesmentioning
confidence: 99%
“…141,144 The benefit of anticoagulating patients structural alterations that may be associated with the undesired outcome of major ventricular arrhythmias or sudden death ( Table 5). 151,152 There is no absolute threshold of the number of PVCs that can be used as a cut-off for underlying disease and hence should trigger further investigations. A study in apparently healthy athletes has shown that in those with >2000 PVC per day, there was a 30% risk of finding underlying heart disease.…”
Section: Consensus Statements Symbol Referencesmentioning
confidence: 99%
“…In a recent meta-analysis of ten studies evaluating exercise-related PVCs during clinical stress testing, exercise-related PVCs correlated with an increased risk of adverse cardiac events, even in asymptomatic patients without overt cardiovascular disease. [16] Interestingly, the sensitivity analyses found that only PVCs seen during the recovery phase of stress testing were associated with adverse outcomes. Notably, these studies did not focus on athletes.…”
Section: Discussionmentioning
confidence: 99%
“…VPCs originating from the outflow tracts and LV fascicles generally do not lead to fatal arrhythmias. The underlying struc- (23,24). Very rarely, the benign PVCs with short coupling interval possess the risk for VT or VF (1).…”
Section: The Characterization Of Pvcsmentioning
confidence: 99%
“…As compared to uniform PVCs, complex PVCs with couplets, triplets, or nonsustained forms, possibly, have a malignant character. Multifocal origins, the increasing number of PVCs with exercise, nonoutflow tract and non-LV fascicular PVCs, PVCs with short coupling intervals or wider PVCs are also carrying a malignant character ( 23 , 24 ). Very rarely, the benign PVCs with short coupling interval possess the risk for VT or VF ( 1 ).…”
Section: Introductionmentioning
confidence: 99%